THU0185 Tofacitinib, An Oral JAK Inhibitor, in The Treatment of Rheumatoid Arthritis: Safety and Clinical and Radiographic Efficacy in Open-Label, Long-Term Extension Studies over 7 Years. (15th July 2016) - Wollenhaupt, J.; Silverfield, J.; Lee, E.B.; Terry, K.K.; Kwok, K.; Lazariciu, I.; Nduaka, C.; Connell, C.A.; DeMasi, R.; Wang, L.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: To report tofacitinib safety, tolerability and clinical response over 84 months (mo), and radiographic data over 12 mo, in long-term extension (LTE) studies. Methods: Data were from two open-label studies (NCT00413699 [ongoing; database unlocked at March 2015 data-cut] and NCT00661661 ]) of patients (pts) with RA who completed randomised Phase (P)1/2/3 tofacitinib studies. Pts received tofacitinib 5 or 10 mg BID as monotherapy or with background DMARDs; data were pooled. Primary endpoints: AEs and lab safety. Confirmed data are reported for decreased Hgb, neutrophil and lymphocyte counts, and increases >50% from BL in creatinine. Secondary endpoints: DAS28-4(ESR), HAQ-DI and mTSS. Safety data were included up to 96 mo and efficacy up to Mo 84 (n≤30 post-Mo 84). Results: 4867 pts were treated (mean [max] duration: 1107 [2895] days). BL data were from P1/P2/P3 index studies for 90.9% of pts. Total tofacitinib exposure was 14926 pt-years (py); 79.2% of pts maintained initial dose. In total, 2132 pts (43.8%) discontinued (AEs: 1051 [21.6%]; insufficient clinical response: 153 [3.1%]). Most common AE classes: infections and infestations (67.6%) and musculoskeletal/connective tissue disorders (37.3%). Most common AEs: nasopharyngitis (18.1%), upper respiratory tract infection (16.2%) and bronchitis (11.7%). SAEs occurred in 26.8% of pts (incidence rate [IR] 9.7/100 py [95% CI 9.2, 10.2]), and serious infection events (SIEs) in 8.4% of pts (IR 2.8/100 py [95% CI 2.5, 3.0]). Malignancies excluding NMSC were reported in 3.0% of pts (IR 1.0/100 py [95% CI 0.8, 1.1]). IRs for SIEs and malignancies through Mo 96 did not increase vs reported data through Mo 84. 1 Decreased Hgb (>30% decrease from BL/Hgb <8 g/dL) occurred in <1.0% of pts. Increased aminotransferases (>3×ULN) occurred in 5.4% (ALT) and 3.1% (AST) of pts. Moderate to severe neutropenia (absolute neutrophil count [ANC] 0.5–1.5×10 3 /mm 3 ) was noted in 1.5% of pts; there were no confirmed cases of ANC <0.5×10 3 /mm 3 . Confirmed absolute lymphocyte counts <0.5×10 3 /mm 3 occurred in 1.3% of pts. Increases >50% from BL in creatinine were seen in 2.4% of pts. Mean DAS28-4(ESR) was 6.29 at BL, 3.74 at Mo 1 and 3.20 at Mo 84. Mean HAQ-DI score was 1.42 at BL, 0.81 at Mo 1 and 0.78 at Mo 84. Radiographic data were available for 1099 pts. Mean mTSS was 24.0 at BL (last P1/P2/P3 index value), 25.1 at Mo 6 and 24.3 at Mo 12. Mean change from BL in mTSS was 0.3 at Mo 6 and 0.2 at Mo 12. Conclusions: Consistent safety and sustained efficacy over 84 mo was seen in pts with RA receiving tofacitinib 5 or 10 mg BID in LTE studies. Changes in mTSS were minimal at Mo 12 in LTE studies. References: Wollenhaupt J et al. Arthritis Rheumatol 2014; 66: S375. Acknowledgement: Previously presented (Wollenhaupt J et al. Arthritis Rheumatol 2015; 67 (S10): 1645) and reproduced with permission. This study was funded by Pfizer Inc. Editorial support was provided by S. Johnson of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: J. Wollenhaupt Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, J. Silverfield Grant/research support from: Pfizer Inc, Speakers bureau: Pfizer Inc, E. B. Lee Consultant for: Pfizer Inc, K. K. Terry Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, I. Lazariciu Consultant for: Pfizer Inc, Employee of: Quintiles Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. A. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. DeMasi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc